OSOBOWE SPÓŁKI JEDNOOSOBOWE - Szczurowski, Tomasz (Zeszyty Prawnicze, 2016)
Single – Partner Partnership Summary The Commercial Companies Code contains regulating of a single – member private limited-liability company and a single – member public company, but partnership can also have single partner. It can not be incorporate as a single – partner partnership, but it is possible that one partner remains in the partnership. First of all, a professional partnership can be single – partner partnerships (art. 98 § 2). However it is the most typical situation, I think that all kind of partnerships may have just one partner. That can happen when the partnership includes two partners and one of them terminates the articles of association or when one of them dies. In this case the partnership would have one partner during liquidation. Although the term of liquidation is unspecified, The Commercial Companies Code does not contains regulating the issue of single – partner partnership. This problem should be solved by applying general norms connecting with liquidation.